Effective lake management of cyanobacteria in changing environments – bridging science and action and group leader of WG3. - Antoniou, Maria G. (My University, 2026)
Cost Action: MC Substitute Member to COST Action CA26958, CYANO-ACTION, Effective lake management of cyanobacteria in changing environments – bridging science and action and group leader of WG3.